Oscillations for Nonlinear Neutral Delay Differential Equations with Variable Coefficients - Fatima N. Ahmed; Rokiah R. Ahmad; Ummul K. S. Din; Mohd S. M. Noorani (Abstract and Applied Analysis)
A class of nonlinear neutral delay differential equations is considered. Some new oscillation criteria of all solutions are derived. The obtained results generalize and extend some of well known previous results in the literature.